2016
DOI: 10.1158/1538-7445.am2016-1491
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 1491: IPH4301, an antibody targeting MICA and MICB exhibits potent cytotoxic activity and immunomodulatory properties for the treatment of cancer

Abstract: MICA and MICB, and ULPB1-6, are ligands for NKG2D, an activating receptor expressed on NK cells and subsets of T cells. Expression of MICA and MICB is induced by cellular stress in transformed tumor cells, upon infections or at sites of chronic inflammation. Their expression is tightly regulated by complex mechanisms both at the mRNA and protein levels. As markers of cellular stress and tumorigenesis, MICA and MICB proteins are attractive candidates for targeting by a cytotoxic antibody. Moreover, ionizing rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…These findings were confirmed when the cytotoxic activity was examined using CD20-expressing Daudi target cells and an anti-CD20 antibody, confirming the trend toward reduced ADCC function mediated by NK derived from the liver compartment and corroborating the interpretation that CD16 expression is critical for optimal ADCC. In order to optimize ADCC and the NKG2D-MICA/B axis, we used a humanized anti-MICA/B mAb, which could on one side stimulate the NK CD16-mediated activity and on the other intercept the binding of NKG2D to the sMICA/B cell-expressed ligand, thus disrupting the interaction between MICA/B and NKG2D, with the ensuing impaired immunosurveillance [43,44]. Our findings showed that anti-MICA/B mAb significantly increased NK-TIL degranulation in the presence of primary human HCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…These findings were confirmed when the cytotoxic activity was examined using CD20-expressing Daudi target cells and an anti-CD20 antibody, confirming the trend toward reduced ADCC function mediated by NK derived from the liver compartment and corroborating the interpretation that CD16 expression is critical for optimal ADCC. In order to optimize ADCC and the NKG2D-MICA/B axis, we used a humanized anti-MICA/B mAb, which could on one side stimulate the NK CD16-mediated activity and on the other intercept the binding of NKG2D to the sMICA/B cell-expressed ligand, thus disrupting the interaction between MICA/B and NKG2D, with the ensuing impaired immunosurveillance [43,44]. Our findings showed that anti-MICA/B mAb significantly increased NK-TIL degranulation in the presence of primary human HCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…gov). The MICA-and MICB-targeting mAb IPH4301 reportedly mediates potent NK cell-stimulatory effects in vitro and in vivo, in the context of transplantable and endogenous tumors, as it prevents NKG2D downregulation on NK cells (Morel et al, 2016). Blocking CD96 with a mAb has been shown to inhibit experimental metastases in three different tumor models, an effect that depended on NK cells, DNAM-1, and IFNG (Blake et al, 2016).…”
Section: Nk Cell Immunotherapy In the Management Of Metastasismentioning
confidence: 99%